2020
DOI: 10.1364/ao.381295
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antimagnetic interference properties and structural optimization of magneto-optical glass current sensors

Abstract: To solve the issue of external magnetic fields interfering with magneto-optical glass current sensors (MOCS), this paper proposes a strip-like splicing structure. First, a mathematical model for integrating the magnetic field strength along the optical path is constructed, and the relationship between the gap size a , the interference source distance d , the angle of the interference source θ , and the relative error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…; ðn ¼ 1;2; 3;4; 5;6Þ: (25) In this case, the zero-magnetic-interference angle of DOCT is independent of the interference distance D, and the ZMI angle is a fixed constant. This means that all positions in the ZMI angle direction outside optical current transducers are ZMI points.…”
Section: Solving For the Zero Magnetic Interference Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…; ðn ¼ 1;2; 3;4; 5;6Þ: (25) In this case, the zero-magnetic-interference angle of DOCT is independent of the interference distance D, and the ZMI angle is a fixed constant. This means that all positions in the ZMI angle direction outside optical current transducers are ZMI points.…”
Section: Solving For the Zero Magnetic Interference Pointmentioning
confidence: 99%
“…The output signals of the two optical sensing structures are added during the measurement to compensate for the error generated by the adjacent phase interference signals to achieve the effect of anticrosstalk magnetic field interference. 25 However, due to the complexity of the structure, using this method creates operational stability problems. Some scholars have analyzed the structural characteristics of the point optical current transducer, differential optical current transducer, and current optical fiber transducer, their found that the crosstalk magnetic field has no effect on the measurement of the optical current transducer at a specific azimuth angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation